2013
DOI: 10.1016/j.ijcard.2012.12.085
|View full text |Cite
|
Sign up to set email alerts
|

T-cell co-stimulation by CD28–CD80/86 and its negative regulator CTLA-4 strongly influence accelerated atherosclerosis development

Abstract: Objective: T-cells are central to the immune response responsible for native atherosclerosis. The objective of this study is to investigate T-cell contribution to post-interventional accelerated atherosclerosis development, as well as the role of the CD28-CD80/86 co-stimulatory and Cytotoxic T-Lymphocyte Antigen (CTLA)-4 co-inhibitory pathways controlling T-cell activation status in this process. Methods and results: The role of T-cells and the CD28-CD80/86 co-stimulatory and CTLA-4 co-inhibitory pathways were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 42 publications
5
70
1
Order By: Relevance
“…The immunoregulatory effect of a soluble fusion protein CTLA-4-Ig may involve blockade of CD80/CD86-CD28 pathway, which is one of the cell extrinsic mechanisms for CTLA-4-mediated immune regulation. Based on previous studies 15,16 and our data, we expect that CTLA-4 may be a possible therapeutic target for atherosclerotic disease. Given that CTLA-4-Ig has been already clinically used and has been shown to be effective for treating patients with rheumatoid arthritis who have high incidence of atherosclerotic cardiovascular disease, our findings imply that an immunomodulatory approach such as costimulatory blockade by CTLA-4-Ig may be effective for treating atherosclerosis and rheumatoid arthritis.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The immunoregulatory effect of a soluble fusion protein CTLA-4-Ig may involve blockade of CD80/CD86-CD28 pathway, which is one of the cell extrinsic mechanisms for CTLA-4-mediated immune regulation. Based on previous studies 15,16 and our data, we expect that CTLA-4 may be a possible therapeutic target for atherosclerotic disease. Given that CTLA-4-Ig has been already clinically used and has been shown to be effective for treating patients with rheumatoid arthritis who have high incidence of atherosclerotic cardiovascular disease, our findings imply that an immunomodulatory approach such as costimulatory blockade by CTLA-4-Ig may be effective for treating atherosclerosis and rheumatoid arthritis.…”
supporting
confidence: 51%
“…15 Moreover, another experimental study demonstrated that CTLA-4-Ig prevented intimal hyperplasia after vascular injury in hypercholesterolemic mice via reduction of Teff responses, and that CTLA-4 blockade using a blocking antibody significantly increased intimal thickening of the injured arteries. 16 Despite these previous studies, the role of CTLA-4 in atherosclerosis has not been fully elucidated.In the present study, we tested the hypothesis that overexpression of CTLA-4 would inhibit the development of atherosclerosis. To address this issue, we generated CTLA-4 transgenic apolipoprotein E-deficient (CTLA-4-Tg/Apoe −/− ) mice where T cells constitutively express CTLA-4 on the cell surface and intracellularly 17 on background prone to develop atherosclerosis.…”
mentioning
confidence: 99%
“…Blockade of CTLA4 expression could promote T cell activation via the CD28/B7 signal pathway. 39 In our in vivo study, upregulation of the expression levels of MHC-II (signal 1) and CD80/CD86 (signal 2) by blockade of CTLA4 promoted T cell activation and proliferation.…”
mentioning
confidence: 66%
“…For example, blocking DC maturation through CD11c-specific knockdown of MyD88 altered the Treg-cell pool and accelerated atherosclerosis. 244 This is further supported by experiments showing that lack of inducible T-cell costimulator or programmed cell death 1, inhibitory pathways of the TNF superfamily, reduces Treg-cell capacity and lead to increased atherosclerosis, as does treatment with CTLA4-Ig (Abatacept), 245,246 which disrupts CD28-CD80/86 interactions. In terms of defining which subsets of cDCs are involved, Choi et al 227 demonstrate that the majority of Flt3 + pre-cDC-derived cells in normal and in atherosclerotic plaques are CD103 + DCs and that Flt3 deficiency increases atheorsclerosis, whereas CCL17 + DCs prevent the differentiation of naïve T cells into Treg cells through CCR4 and thus promote atherosclerosis.…”
Section: Functional Roles For Dcs In Atherosclerosismentioning
confidence: 93%